Mecanismos de coesão referencial na produção escrita de alunos concluintes do ensino fundamental - Costa, Elis Betânia Guedes da (2010)
This work aims to identify, describe and analyze the main mechanisms of reference present in the texts produced by students that are finishing their fundamental school. With this in mind, we observe 46 Portuguese classes. The class was in its 9th Fundamental level, in a public school of the Cruzeta, RN. In this period, we collected our corpus that is composed by the papers that students produced. This research has an ethnographic approach and it has as theoretical support some studies about some mechanisms of reference, specifically, the lexical repetition and anaphor. In general, we are based on the studies about cohesive mechanisms from authors as Adam (2008); Beaugrande and Dressler (1981, 1997); Koch (1999, 2004, 2005, 2008), Marcuschi (1983, 1992, 2005, 2006); Bessa Neto (1991) and Neves (2006). In the corpus, we could identify some lexical repetitions (literal, with estrutural variation), as well as, anaphors, mainly pronominal ones. Then, we can notice that most students have showed difficulties in the use of those mechanisms of reference as a strategy of textual progression